Prenatal Perfluorooctanoic Acid (PFOA) Exposure Is Associated With Lower Infant Birthweight Within the MADRES Pregnancy Cohort - Peterson, Alicia K.; Eckel, Sandrah P.; Habre, Rima; Yang, Tingyu; Faham, Dema; Farzan, Shohreh F.; Grubbs, Brendan H.; Kannan, Kurunthachalam; Robinson, Morgan; Lerner, Deborah; Al-Marayati, Laila A.; Walker, Daphne K.; et al. (Frontiers in Epidemiology, 2022)
Introduction Per- and polyfluoroalkyl substances (PFAS) are persistent synthetic chemicals found in household products that can cross the placenta during pregnancy. We investigated whether exposure to PFAS during pregnancy were associated with infant birth outcomes in a predominately urban Hispanic population. Methods Serum concentrations of perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS), perfluorohexanesulphonic acid (PFHxS), perfluorononanoic acid (PFNA), and perfluorodecanoic acid (PFDA) were measured in 342 prenatal biospecimens (mean gestational age: 21±9 weeks) from participants in the ongoing Maternal And Developmental Risks from Environmental and Social Stressors (MADRES) cohort. PFAS compounds were modeled continuously or categorically depending on percentage of detected samples. Birth outcomes assessed were birthweight, gestational age at birth, and birthweight for gestational age (BW-for-GA) z-scores that accounted for parity or infant sex. Single pollutant and multipollutant linear regression models were performed to evaluate associations between PFAS exposures and birth outcomes adjusting for sociodemographic, perinatal, and study design covariates. Results Maternal participants (n=342) were on average 29±6 years old at study entry and were predominantly Hispanic (76%). Infants were born at a mean of 39±2 weeks gestation and weighed on average 3,280±523 grams. PFOS and PFHxS were detected in 100% of samples while PFNA, PFOA, and PFDA were detected in 70%, 65%, and 57% of samples, respectively. PFAS levels were generally lower in this cohort than in comparable cohorts. Women with detected levels of PFOA during pregnancy had infants that weighed on average 119.7 grams less (95% CI -216.7, -22.7) than women with undetected levels of PFOA in adjusted single pollutant models. PFOA results were also statistically significant in BW-for-GA z-score models that were sex or parity specific. In models that mutually adjusted for five detected PFAS compounds, PFOA results remained comparable; however, the association was only significant in BW-for-GA z-scores that were parity specific (β= -0.3; 95% CI -0.6, -0.01). We did not find significant adjusted associations with the remaining PFAS concentrations and the birth outcomes assessed. Conclusion Prenatal exposure to PFOA was associated with lower birthweight in infants, suggesting that exposure to these chemicals during critical periods in development may have important implications for children’s health.